Comparative Pathology and Pathogenesis of African Swine Fever Infection in Swine - Salguero, Francisco J. (Frontiers in Veterinary Science, 2020)
African Swine Fever (ASF) is a viral disease that affects animals of the Suidae family, and soft ticks from the genus Ornithodoros can also be infected by the ASF virus (ASFV). The disease was first described in Africa at the beginning of the twentieth century as an acute disease characterised by high mortality and fatal haemorrhages. ASF has caused outbreaks in numerous countries and it continues to be devastating nowadays for the porcine sector in those countries affected, and a massive threat for those free of the disease. ASF can follow clinical courses from peracute to chronic in domestic pigs (Sus scrofa) depending on a variety of factors, including the immune status of the animals and the virulence of the ASFV strain. The key features of the pathogenesis of the disease in domestic swine are a) a severe lymphoid depletion including lymphopenia and a state of immunodeficiency, and b) haemorrhages. However, African wild swine like bushpigs (Potamochoerus larvatus), red river hogs (Potamochoerus porcus) and warthogs (Phacochoerus africanus) can be infected by ASFV showing no clinical signs of disease and acting as natural reservoir hosts. In this article we review the key features of the gross and microscopic pathology together with a description of the pathogenesis of ASFV infection in domestic pigs following the different clinical courses. The pathogenesis of ASF in wild and domestic swine is also described, what can provide important information for the design of control strategies, such as vaccines.